THE COMPARISON OF LEVEL OF COSTUMERS SATISFACTION TOWARD AN INTERPERSONAL COMMUNICATION OJEK ONLINE AND OFFLINE IN BATAM - Sri Afridola; Hikmah Hikmah (Jurnal Apresiasi Ekonomi, 2018)
One business that is developing today is the business of transportation services by motorcycle or used to be called an ojek. If the first motorcycle taxis are managed conventionally and sole proprietorship, now there is a new business motor that is a commercial business, which provides public transportation services and managed professionally. Currently there are two kinds of ojek services, namely ojek offline and ojek online. Unlike conventional motorcycles that can only be found when consumers look for it at certain points, ojek online can be ordered online through android apps. The purpose of this research is to know the comparison of consumer satisfaction level on interpersonal communication on ojek online and offline. The population used is the people of Batam who use Online Ojek and Ojek offline. The population consists of 5 districts namely Batuaji, Sagulung, Sekupang, Batu ampar and Batam Kota with a sample of 384 respondents. The results obtained by using questionnaires / questionnaires. Data analysis used is different test with SPSS version 20. The result of research shows that consumer satisfaction level on communication interpersonal with indicator of openness, empathy, support, positive and equality on ojek online and offline there is difference. Overall the level of customer satisfaction on communication interpersonal ojek online and offline there is a difference, with Sig count 0.000> 0.005. So it can be concluded that there is a difference in the level of customer satisfaction on communications interpersonal services ojek online and offline in Batam. Keywords: Costumers satisfaction, Interpersonal communication